Biophysical studies on the RNA cores of satellite tobacco mosaic virus. - Day, J (2001)
Satellite tobacco mosaic virus (STMV) was probed using a variety of proteases. Consequences of the degradation were analyzed using gel electrophoresis, quasi-elastic light scattering (QELS), and atomic force microscopy (AFM). Proteolysis rates of 30 minutes for complete degradation of the protein capsid, up to many hours, were investigated. With each protease, degradation of virions 17 nm in diameter was shown by QELS to result in particles of 10 nm diameter, which is that of the RNA core observed in the virion by x-ray diffraction analysis. This was verified by direct visualization with atomic force microscopy. Using QELS, it was further shown that freshly prepared RNA cores remain as individual, stable, 10-nm condensed particles for 12 to 24 h. Clusters of particles then formed, followed by very large aggregates of 500 to 1000 nm diameter. AFM showed that the aggregates were composed of groups of the condensed RNA cores and were not due to unfolding of the nucleic acid. No unfolding of the core particles into extended conformation was seen by AFM until the samples were heated well beyond 90 degrees C. Mass spectrometry of RNA core particles revealed the presence of a major polypeptide whose amino acid sequence corresponded to residues 2 through 25 of the coat protein. Amino acids 13 through 25 were previously observed to be in direct contact with the RNA and are presumably protected from protease digestion. Low resolution difference Fourier analyses indicated the courses of the remainders of the amino terminal strands (amino acids 2-12) in intact virions. Any individual strand appears to have several choices of path, which accounts for the observed disorder at high resolution. These positively charged strands, serving as virtual polyamines, engage the helical segments of RNA. The intimate association of amino acid residues 2 through 25 with RNA likely contributes to the stability of the condensed conformation of the nucleic acid cores.